Physical Activity and Sport in Acculturation Processes in Immigrant Women: A Systematic Review - Ana Blanco-Ayala; Roshan Galvaan; Jesús Fernández-Gavira (Societies)
Acculturation is a key process in the adaptation of immigrant women to their host countries, influenced by social, cultural, and structural factors. Physical activity and sport have been identified as potential tools to facilitate this transition, promoting social inclusion and cultural adaptation. This systematic review, following the PRISMA guidelines and the Cochrane Handbook, analyzed empirical and conceptual studies published in English since 2000 from Scopus, Web of Science, SPORTDiscus, and ERIC. Inclusion criteria encompassed studies examining the relationship between physical activity, sport, and acculturation in immigrant women, while excluding non-empirical research, studies focusing exclusively on men or children, and those published in languages other than English. A total of 17 studies met the eligibility criteria. Thematic analysis revealed four key dimensions: (1) the bidirectional relationship between acculturation and sport participation, (2) gender and cultural barriers, (3) socio-economic and structural determinants, and (4) the impact on health and psychosocial well-being. The review highlights the role of physical activity in fostering social capital and integration while identifying persistent barriers such as cultural norms, economic constraints, and policy limitations. Although findings support the positive impact of these activities, further research is needed to address intersectional challenges and structural inequalities.